1997
DOI: 10.1074/jbc.272.24.15275
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Determination of Replication Origins of Human Mitochondrial DNA by Ligation-mediated Polymerase Chain Reaction

Abstract: A large part of replication is aborted in human mitochondria, the result being a D-loop. As few attempts have been made to distinguish free 5 ends of true replicate from those of abortive ones, we examined the 5 ends of true replicate of human mitochondrial DNA at one nucleotide resolution in vivo by making use of ligation-mediated polymerase chain reaction. The distribution and relative amounts of origins of the true replicate are exactly the same as those of total newly synthesized heavy strands, which means… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

14
88
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 96 publications
(102 citation statements)
references
References 19 publications
14
88
0
Order By: Relevance
“…Fractionation by sodium-borate gelelectrophoresis resolved four 7S DNA species of ∼560-650 nt, which are concordant with those defined previously (8) with free 5′ ends mapping to np 111, 150, 168, and 191 (23). Treatment with RNase HI did not alter their lengths (Fig.…”
supporting
confidence: 89%
“…Fractionation by sodium-borate gelelectrophoresis resolved four 7S DNA species of ∼560-650 nt, which are concordant with those defined previously (8) with free 5′ ends mapping to np 111, 150, 168, and 191 (23). Treatment with RNase HI did not alter their lengths (Fig.…”
supporting
confidence: 89%
“…Ligation-mediated PCR: LMPCR was performed according to previously described methods (Mueller et al 1992;Kang et al 1997). The primers used in this study are shown in Figure 1.…”
Section: Methodsmentioning
confidence: 99%
“…These are located around the O R and are widely conserved among vertebrate species. Immediately upstream of the O R of the H-strand, conserved sequence blocks (CSBs) are present and are suggested to be responsible for the initiation of the H-strand replication (Tapper and Clayton 1981;Cairns and Bogenhagen 1986;King and Low 1987;Kang et al 1997). CSBs are thought to be involved in generating the 39 ends of the RNA primers, which are required for the DNA synthesis of the H-strand (Shadel and Clayton 1997;Taanman 1999).…”
Section: Etazoan Mitochondrial Dna (Mtdna) Is Amentioning
confidence: 99%
See 1 more Smart Citation
“…DNA synthesis from O H is unidirectional and proceeds to displace the parental heavy strand (H-strand). After leading-strand synthesis has reached two-thirds of the genome, it activates O L and lagging-strand DNA synthesis then initiates in the opposite direction (2)(3)(4). Recently, analysis of mtDNA replication intermediates by atomic force microscopy revealed that the strand-displacement model is an oversimplification and that additional initiation sites for lagging-strand mtDNA synthesis exist on the light strand (L-strand) (5).…”
mentioning
confidence: 99%